Consumers Attitude Towards Skippable ADS on Youtube Trueview In-Stream - an Empirical Study Among College Students in Bandung - Saputra, Tejo Sandi; Fachira, Ira (Journal of Business and Management, 2014)
This study focuses on how young people respond to the YouTube TrueView in-stream as well as the factors that influence. Here, the ad will appear before the original video is playing and has an option "skip" on the ad that will be available after the first 5 seconds. Questionnaire containing demographic, YouTube users' habits, and by adapting the theory of Brackett & Carr (2001) which states that the buyer's attitude toward an ad is influenced by entertainment, informativeness, irritation, credibility and relevant demography, coupled with questions about their attitudes and their reason. The questionnaire was filled in by 150 respondents, undergraduate students of Institut Teknologi Bandung and Universitas Padjadjaran, aged 17-22 years old who have ever visited YouTube. Then the data were analyzed using IBM SPSS 19 for Windows through descriptive analysis, reliability, validity, cross tabulations, multiple regressions, multicollinearity test, autocorrelation test, and normality test. Data showed that there is an influence of the ad entertainment, ad irritation, and ad credibility in the buyer's attitude towards YouTube TrueView in-stream. Ad entertainment has constants bigger than the other two factors. Ad entertainment and ad credibility has a positive relationship, while the ad irritation has a negative relationship. Ad informativeness and relevant demography has no influence on a undergraduate student's decision to skip the ad or not. From all these findings obtained that students always or frequently pass through an ads that appear, this attitude can be interpreted negatively because it does not fit the expectations and goals of the advertiser.Keywords: marketing, consumers' attitude, advertising, YouTube TrueView